THE RELATIONS OF FORMAL THINKING ABILITY AND INQUIRY APPROACH IN SCIENCE LEARNING - Arifah Fitriyah, Lina (ERUDIO (Journal of Educational Innovation), 2013)
Abstract The science learning includes on learning process and product. Improving the quality of science learning that emphasizes the learning process can be done by giving the scientific work experience to students.Thinking skills of learners to be one of life skills that are needed to address the increasingly complex problems of life in the information age. Teachers are expected to plan and implement accommodate learning thinking skills.Formal thinking skills is the ability of learners to receive intellectual stimulations in the process of science learning concepts microscopic properties. Formal thinking skills give a small role in the ability inkuri someone. The suitable approach to improve the ability of intellectual inquiry is inquiry approach. Using a inquiry approach in laboratory-based, students have many opportunities to obtain data directly, interpret data, create hypotheses, test these hypotheses and discuss them to draw a conclusion. In guided inquiry learning approach,students are also more stimulated to find their own concepts in science.The students who have already begun to enter the formal level of thinking has been able to develop their own skills to find something that can be used to solve the problems faced.   Keywords: formal thinking skills, inquiry approach